اتجاهات مديري المدارس الابتدائية نحو مهام مشرفي التربية بمرحلة التعليم الابتدائي دراسة ميدانية بولاية بجاية - بورحلي مراد; بتقة مراد; اشراف: عرعار غنية (جامعة محمد بوضياف -المسيلة, 2025)
تهدف الدراسة الحالية إلى معرفة طبيعة اتجاهات مديري المدارس الابتدائية نحو مهام مشرفي التربية بمرحلة التعليم الابتدائي، والتعرف على الفروق حسب متغير : الجنس ، الخبرة المهنية و المؤهل العلمي ، حيث تكونت عينة البحث من 166 مديرا تم اختيارهم عن طريق المسح السامل ، و لتحقيق اهداف البحث استخدم الطالبان استبيان من تصميمهما ، و باستخدام المنهج الوصفي التحليلي ، و بعد المعالجة الإحصائية عن طريق برنامج الحزمة الإحصائية للعلوم الاجتماعية ( SPSS) تم التوصل إلى النتائج التالية : - يبدي مدراء المدارس الابتدائية اتجاهات إيجابية نحو مهام مشرفي التربية بمرحلة التعليم الابتدائي بولاية بجاية . - لا توجد فروق ذات دلالة إحصائية في اتجاهات مديري المدارس الابتدائية بولاية بجاية نحو مهام مشرفي التربية بمرحلة التعليم الابتدائي يعزى لمتغير الجنس . - لا توجد فروق ذات دلالة إحصائية في اتجاهات مديري المدارس الابتدائية بولاية بجاية نحو مهام مشرفي التربية بمرحلة التعليم الابتدائي يعزى لمتغير الخبرة المهنية . - لا توجد فروق ذات دلالة إحصائية في اتجاهات مديري المدارس الابتدائية بولاية بجاية نحو مهام مشرفي التربية بمرحلة التعليم الابتدائي يعزى لمتغير المؤهل العلمي . الكلمات المفتاحية : الاتجاهات - مديرو المدارس الابتدائية – مهام – مشرف التربية – مرحلة التعليم الابتدائي .   الملخص بالإنجليزية: Study summary: Study title: Primary school principals’ attitudes towards the tasks of education supervisors in the primary education stage: A field study in the state of Bejaia. The current study aims to know the nature of the attitudes of primary school principals towards the tasks of educational supervisors in the primary education stage, and to identify differences according to the variables: gender, professional experience and academic qualification, as the research sample consisted of 166 principals who were selected through a comprehensive survey, and to achieve the objectives of In the research, the two students used a questionnaire they designed, using the descriptive analytical method, and after statistical processing using the Statistical Package for the Social Sciences (SPSS) program, the following results were reached: -Primary school principals show positive attitudes towards the tasks of education supervisors in the primary education stage in the state of Bejaia. - There are no statistically significant differences in the attitudes of primary school principals in the state of Bejaia towards the tasks of education supervisors in the primary education stage due to the gender variable. - There are no statistically significant differences in the attitudes of primary school principals in the state of Bejaia towards the tasks of education supervisors in the primary education stage due to the variable of professional experience. - There are no statistically significant differences in the attitudes of primary school principals in the state of Bejaia towards the tasks of education supervisors in the primary education stage due to the academic qualification variable. Keywords: trends - primary school principals - tasks - education supervisor - primary education stage